CompTIA Linux+/LPIC-1 portable command guide : all the commands for the CompTIA LX0-103 & LX0-104 and LPI 101-400 & 102-400 exams in one compact, portable resource - Rothwell, William (Pearson IT Certification, 2018)
Here are all the CompTIA Linux+/LPIC-1 Linux commands you need in one condensed, portable resource. The CompTIA Linux+/LPIC-1 Portable Command Guide is filled with valuable, easy-to-access information and is portable enough to use wherever your work takes you. The guide summarizes all Linux+/LPIC-1 certification-level Linux commands, keywords, command arguments, and associated prompts, and provides tips and examples of how to apply them to real-world scenarios. Configuration examples throughout the book provide you with a better understanding of how these commands are used in real-world environments. This book reflects topics in today's CompTIA LX0-103 & LX0-104 and LPI 101-400 & 102-400 exams. Use this quick reference resource to help you memorize commands and concepts as you work to pass any of these CompTIA or LPI certification exams. The book is organized into these parts: Exam LX0-103/LPI 101-400 Part I: System Architecture Part II: Linux Installation and Package Management Part III: GNU and Unix Commands Part IV: Devices, Linux Filesystems, Filesystem Hierarchy Standard Exam LX0-104/LPI 102-400 Part V: Shells, Scripting, and Data Management Part VI: User Interfaces and Desktops Part VII: Administrative Tasks Part VIII: Essential System Services Part IX: Networking Fundamentals Part X: Securityuick, offline access to all CompTIA Linux+/LPI LPIC-1 commands for research and solutions Logical how-to topic groupings for a one-stop resource Great for review before your Linux+ or LPIC-1 certification exams Compact size makes it easy to carry with you, wherever you go "Create Your Own Journal" appendix with blank, lined pages allows you to personalize the book for your needs "What Do You Want to Do?" chart inside front cover helps you to quickly reference specific tasks.